Drug Discovery of DKK1 Inhibitors - Jiang, Hewen; Zhang, Zongkang; Yu, Yuanyuan; Chu, Hang Yin; Yu, Sifan; Yao, Shanshan; Zhang, Ge; Zhang, Bao-Ting (Frontiers in Pharmacology, 2022)
Dickkopf-1 (DKK1) is a well-characterized Wnt inhibitor and component of the Wnt/β-catenin signaling pathway, whose dysregulation is associated with multiple abnormal pathologies including osteoporosis, Alzheimer’s disease, diabetes, and various cancers. The Wnt signaling pathway has fundamental roles in cell fate determination, cell proliferation, and survival; thus, its mis-regulation can lead to disease. Although DKK1 is involved in other signaling pathways, including the β-catenin-independent Wnt pathway and the DKK1/CKAP4 pathway, the inhibition of DKK1 to propagate Wnt/β-catenin signals has been validated as an effective way to treat related diseases. In fact, strategies for developing DKK1 inhibitors have produced encouraging clinical results in different pathological models, and many publications provide detailed information about these inhibitors, which include small molecules, antibodies, and nucleic acids, and may function at the protein or mRNA level. However, no systematic review has yet provided an overview of the various aspects of their development and prospects. Therefore, we review the DKK1 inhibitors currently available or under study and provide an outlook on future studies involving DKK1 and drug discovery.